The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1111/j.1748-8583.2003.tb00090.x
|View full text |Cite
|
Sign up to set email alerts
|

The rise of the ‘network organisation’ and the decline of discretion

Abstract: This article explores the implications of ‘networked’ and ‘flexible’ organisations for the work and skills of professionals/ Drawing on material from four different case studies, it reviews work that is outsourced (involving IT professionals and housing benefit caseworkers), work that is done by teachers contracted to a temporary employment agency and work organised through an inter‐firm network (chemical production workers). In each case work that was outsourced was managed very differently to that undertaken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Clark and Colling [63], who have conducted in depth case studies in the engineering contracting industry, find that the role of the HRM function is changing and that these changes are not reflected in the HRM literature because there is a lack of engagement between project management literature and HRM literature on the role of HRM practices in project-oriented companies. We share these observations, as for example in the literature on HRM in flexible firms such as the network organization [64], where there is no explicit mention of projects or their impact on HRM in project-oriented companies. The HR implications of project management as a core business process of organizing work and the project-oriented company as such are not objects of consideration in the leading HRM publications we have investigated which is surprising given increasing evidence that project oriented working is becoming increasingly important [16,65,66], and that this is a development that need to be considered carefully and critically in terms of the implications from non-managerial as well as managerial perspectives [67].…”
Section: Emerging Interest In Project-oriented Companiesmentioning
confidence: 83%
“…Clark and Colling [63], who have conducted in depth case studies in the engineering contracting industry, find that the role of the HRM function is changing and that these changes are not reflected in the HRM literature because there is a lack of engagement between project management literature and HRM literature on the role of HRM practices in project-oriented companies. We share these observations, as for example in the literature on HRM in flexible firms such as the network organization [64], where there is no explicit mention of projects or their impact on HRM in project-oriented companies. The HR implications of project management as a core business process of organizing work and the project-oriented company as such are not objects of consideration in the leading HRM publications we have investigated which is surprising given increasing evidence that project oriented working is becoming increasingly important [16,65,66], and that this is a development that need to be considered carefully and critically in terms of the implications from non-managerial as well as managerial perspectives [67].…”
Section: Emerging Interest In Project-oriented Companiesmentioning
confidence: 83%
“…11 Grugulis, Vincent, and Hebson (2003) examined outsourcing in three functions requiring radically different levels of skill and complexity and found that in each 338 Brookings Trade Forum: 20057. Pine (1993.…”
Section: In-house Versus Outsourced Strategiesmentioning
confidence: 99%
“…Also, there were strongly institutionalized practices that were common to both organizations and these increased the scope for cooperation, creating wide-ranging benefits and increased potential for mutual organizational learning (Hunter et al, 1996; also see Grugulis et al, 2003). Here, inter-organizational cooperation was increased by resource dependencies existing between the organizations, a situation likely to occur elsewhere.…”
Section: Discussionmentioning
confidence: 99%